Circadian Responses to Light in the BTBR Mouse. Issue 5 (October 2022) - Vijaya Shankara, Jhenkruthi; Horsley, Katelyn G.; Cheng, Ning; Rho, Jong M.; Antle, Michael C.
Animals with altered freerunning periods are valuable in understanding properties of the circadian clock. Understanding the relationship between endogenous clock properties, entrainment, and influence of light in terms of parametric and non-parametric models can help us better understand how different populations adapt to external light cycles. Many clinical populations often show significant changes in circadian properties that in turn cause sleep and circadian problems, possibly exacerbating their underlying clinical condition. BTBR T + Itpr3 tf /J (BTBR) mice are a model commonly used for the study of autism spectrum disorders (ASD). Adults and adolescents with ASD frequently exhibit profound sleep and circadian disruptions, including increased latency to sleep, insomnia, advanced and delayed sleep phase disorders, and sleep fragmentation. Here, we investigated the circadian phenotype of BTBR mice in freerunning and light-entrained conditions and found that this strain of mice showed noticeably short freerunning periods (~22.75 h). In addition, when compared to C57BL/6J controls, BTBR mice also showed higher levels of activity even though this activity was compressed into a shorter active phase. Phase delays and phase advances to light were significantly larger in BTBR mice. Despite the short freerunning period, BTBR mice exhibited normal entrainment in light-dark cycles and accelerated entrainment to both advanced and delayed light cycles. Their ability to entrain to skeleton photoperiods of 1 min suggests that this entrainment cannot be attributed to masking. Period differences were also correlated with differences in the number of vasoactive intestinal polypeptide–expressing cells in the suprachiasmatic nucleus (SCN). Overall, the BTBR model, with their unique freerunning and entrainment properties, makes an interesting model to understand the underlying circadian clock.